2002
DOI: 10.2176/nmc.42.237
|View full text |Cite
|
Sign up to set email alerts
|

Upper Plexus Thoracic Outlet Syndrome. Case Report.

Abstract: A 47-year-old right-handed female became aware of proximal ache and muscle weakness in the right shoulder and elbow in 1997. Atrophy of the right biceps muscle was recognized and the right deltoid, triceps, supraspinatus, and infraspinatus muscles were weak. The Morley test and elevated arm stress test were positive. Neurolysis of the brachial plexus and anterior scalenectomy were performed via a right supraclavicular approach. An abnormal fibromuscular band was identified passing between the upper and middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The ASM is also implicated in the distribution of nerves comprising the brachial plexus. As previously mentioned (Roos, ; Wood and Ellison, ; Urschel and Razzuk, ; Matsuyama et al, ), upper plexus TOS is seen in 3–12% of nTOS cases. This is likely a result of the multitude of variations seen between C5/C6 and the ASM.…”
Section: Anatomy and Embryologymentioning
confidence: 63%
See 1 more Smart Citation
“…The ASM is also implicated in the distribution of nerves comprising the brachial plexus. As previously mentioned (Roos, ; Wood and Ellison, ; Urschel and Razzuk, ; Matsuyama et al, ), upper plexus TOS is seen in 3–12% of nTOS cases. This is likely a result of the multitude of variations seen between C5/C6 and the ASM.…”
Section: Anatomy and Embryologymentioning
confidence: 63%
“…Two recent case reports are of clinical relevance to TOS. Matsuyama et al () reported a patient with atrophy of the right biceps muscle, as well as weakness in the deltoid, triceps, supraspinatus, and infraspinatus muscles. The case was diagnosed as upper plexus TOS because of C5–C7 nerve root compression.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Rapid improvement in functional parameters after neurolysis has been described in humans and experimental animals [7,8], including anecdotal case reports involving the long thoracic nerve [4], and ulnar nerve [9]. It is difficult to measure the outcome of surgical procedures when relying on the patients' subjective reports or on postoperative electrical testing, which does not always correlate Abduction improvements one day post surgery with function [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the superior piercing variant would cause neurologic symptoms in the C5 and C6 dermatomal distribution of the lateral arm, thumb, and second digit. Specifically, weakness and sensory deficits in the first two digits, and diminished reflexes of the biceps brachii and brachioradialis muscles [25,26,27,28]. The multiple piercing variant (Figure 2C) would result in more extensive neurogenic issues, corresponding with symptoms along the C5, C6, and C7 dermatomes, affecting the first through third digits of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple piercing variant (Figure 2C) would result in more extensive neurogenic issues, corresponding with symptoms along the C5, C6, and C7 dermatomes, affecting the first through third digits of the hand. The clinical consequences could also include additional muscle weakness or decreased reflexes in the triceps brachii muscle [26,27,28]. …”
Section: Discussionmentioning
confidence: 99%